The value of phonetics and pronunciation teaching for advanced learners of English - Brekelmans, Gwen (Linguistica (Ljubljana), 2017)
Pronunciation is an essential part of acquiring a second language, but far too often little time is spent on teaching it (Kelly 1969). It seems as if it is generally thought that pronunciation is something that will develop on its own, yet learners are still assumed to maintain a certain level. This paper investigates the effects of explicit pronunciation and phonetics teaching on the English speech production of advanced Dutch learners of English. The pronunciation of advanced university learners was investigated at several points over a period of three years, halfway during which their pronunciation teaching was stopped. The effect this termination had on their speech production was investigated, as well as any task-specific differences in read versus spontaneous speech. Also studied was the potential influence of studying abroad and taking English-taught courses. Overall, this study shows that explicit teaching has a clear effect on the pronunciation of the learners. Some features of pronunciation turn out to be more robust than others, and the task type has an unmistakeable influence on the native-like quality of the learners% pronunciation, while there was only a minor effect of general exposure to English. Altogether, the value of explicit phonetics and pronunciation teaching turns out to be quite high for advanced second language learners, and once they acquire a certain level they are able to maintain a stable accent.
Keywords: angleščina; didaktika jezika; English; fonetika; izgovorjava; phonetics; tuji jeziki